Progress in endophytic fungi secondary metabolites: biosynthetic gene cluster reactivation and advances in metabolomics - Rahmat Folashade Zakariyah; Kamoldeen Abiodun Ajijolakewu; Ayomide Joseph Ayodele; Barnabas Ipinnuoluwa Folami-A; Elohor Precious Samuel; Sabdat Omeneke Otuoze; Lukman Bola Abdulrauf; Risikat Nike Ahmed (Bulletin of the National Research Centre, 2024)
Abstract Background Fungal endophytes exhibit symbiotic relationships with their host plants but have recently emerged as sources for synthesizing important varieties of secondary metabolites (SMs). Many of these metabolites have shown significant importance as antibacterial, antifungal, antitumor, and anticancer drugs, leading to their exploration in medicine and pharmaceuticals. Main body of the abstract The endophytes' biosynthetic gene clusters (BGCs) are responsible for encoding enzymes that produce these SMs. The fungal endophytes' ability has been challenged due to their inability to trigger cryptic BGCs and their loss of ability to produce secondary metabolites over an extended period in an artificial culture medium. This review investigates the array of SMs produced by endophytic fungi. It identifies methods for awakening and exploiting silent BGCs to produce novel natural metabolites and explores recent advancements in metabolomics platforms used to profile SMs. Silent BGCs can be activated using various methods, including co-cultivation, one strain of many compounds, epigenetic modification, heterologous expression, and cluster-specific transcription factor methods. Short conclusion These methods reviewed effectively enhance the production of silent BGCs, leading to a significant increase in secondary metabolite production. Meanwhile, metabolomics profiling using liquid or gas chromatography coupled with mass spectrometry could provide several chances to discover bioactive compounds' complexity and chemical diversity. This review has, thus, given insight into the significance of methods used to reactivate BGCs from endophytes and the importance of varying techniques of their metabolomic profiling.